2021
DOI: 10.1186/s12911-021-01410-3
|View full text |Cite
|
Sign up to set email alerts
|

Clinical data mining on network of symptom and index and correlation of tongue-pulse data in fatigue population

Abstract: Background Fatigue is a kind of non-specific symptom, which occurs widely in sub-health and various diseases. It is closely related to people's physical and mental health. Due to the lack of objective diagnostic criteria, it is often neglected in clinical diagnosis, especially in the early stage of disease. Many clinical practices and researches have shown that tongue and pulse conditions reflect the body's overall state. Establishing an objective evaluation method for diagnosing disease fatigu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 35 publications
1
7
0
Order By: Relevance
“…In this study, the measurement model consisted of the formative measurement model (for obesity) and the reflective measurement model (for routine blood tests, lipid metabolism, liver function and characteristics of SV). We evaluated the inner model by estimating the path coefficients between latent variables, discriminant validity, significance values, etc., and evaluated the outer model by confirming the reliability and validity of the measurement indicators, ultimately, to verify the reasonableness of the assumed relationship in the model 22 .…”
Section: Resultsmentioning
confidence: 99%
“…In this study, the measurement model consisted of the formative measurement model (for obesity) and the reflective measurement model (for routine blood tests, lipid metabolism, liver function and characteristics of SV). We evaluated the inner model by estimating the path coefficients between latent variables, discriminant validity, significance values, etc., and evaluated the outer model by confirming the reliability and validity of the measurement indicators, ultimately, to verify the reasonableness of the assumed relationship in the model 22 .…”
Section: Resultsmentioning
confidence: 99%
“…Our research team has been continuously working on research related to tongue diagnosis technology and has established a relatively reliable analysis methodology for tongue and index, and has also published findings on tongue diagnosis (Zhang et al, 2017;Qiao et al, 2018;Li et al, 2021a,b;Shi et al, 2021). The index of tongue diagnosis mainly included the color and texture of tongue body and tongue coating and proportion of tongue coating.…”
Section: Discussionmentioning
confidence: 99%
“…Health Status Assessment Questionnaire Scale (H20 Scale) and the Information Record Form of Four Diagnosis of TCM (Copyright No. : 2016Z11L025702) (Shi et al, 2021) (as shown in Supplementary Material 1) were used to further define the state of fatigue.…”
Section: Inclusion and Exclusion Criteriamentioning
confidence: 99%
See 1 more Smart Citation
“…Fatigue is one of the most common subhealth conditions (Shi et al, 2021). A previous study has found that the prevalence of fatigue among nurses was 61.5% (Fang et al, 2013).…”
Section: Introductionmentioning
confidence: 99%